Effect of Fiber Volume Fraction Of Tensile Strength and Impact Strength biocomposite of Bacterial cellulose-Shellac - Dini Cahyandari (Universitas Muhammadiyah Semarang, 2016)
Abstract. Composites materials usually consist of reinforcement or filler by glass or carbon fiber and the polymer matrixmade of petroleum. These materials are not appropriate because it cant be degradated by environment and need alot ofenergy to produce them. Their waste only can be burned to produce CO2 and CO that caused global warming. Thereforresearch on biocomposites, that more environmental friendly are needed. The objective of this study is to investigated theeffect of volume fraction of fiber on tensile and impact strength of bacterial cellulose fiber reinforced shellac biocomposites. This research is focus on biocomposites of bacterial cellulose and shellac. Bacterial cellulose is cellulose that produced from bacteria Acetobacter Xylinum. Medium that used in this research is tapioka water. Shellac is secretion of lac bug.Bacterial cellulose reinforced shellac biocomposites obtained by blending nata de cassava gel and shellac until become slurry. Volume fraction of bacterial cellulose are 0%, 30%, 50% and 60%. The result showed that the optimal tensile strength of biocomposites is the 60%. highest impact strength is obtained on 50% of bacterialcellulose.